2016
DOI: 10.4102/phcfm.v8i2.953
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of caesarean-section delivery in Addis Ababa, Ethiopia

Abstract: SettingThe study was conducted in Addis Ababa, the capital city of Ethiopia. Specifically, it was conducted in all healthcare facilities offering maternity and obstetric services.ObjectiveThe objective of the study was to explore the patterns of caesarean-section (CS) delivery in Addis Ababa.MethodsA cross-sectional survey was carried out between December 2013 and January 2014. The population for the study were women aged between 15 and 19 years of age who had given birth in the last 1–3 years before the date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 14 publications
8
25
5
Order By: Relevance
“…Our ndings were comparable with previous study reports, where Addis Ababa, Harar and Dire Dawa had the highest CS rates and Somali region the lowest 40 . In line with our ndings, several previous hospitalbased studies revealed that CS rates were very high in these urban centers 38,40,41 . These regional disparities may be attributed to better access to surgical services with overuse of the procedure and higher prevalence of elective CS in large cities of the country 6 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our ndings were comparable with previous study reports, where Addis Ababa, Harar and Dire Dawa had the highest CS rates and Somali region the lowest 40 . In line with our ndings, several previous hospitalbased studies revealed that CS rates were very high in these urban centers 38,40,41 . These regional disparities may be attributed to better access to surgical services with overuse of the procedure and higher prevalence of elective CS in large cities of the country 6 .…”
Section: Discussionsupporting
confidence: 93%
“…It is also lower than a CS rate of 27.6% in Attat Hospital in southern Ethiopia, 37 . The rate of CS in Addis Ababa city administration is much higher than the nding of a previous study, where a CS rate of 19.2% was reported 38 , although the most recent study reported a comparable CS rate (38.3%) in the city 39 . Our study included data from all hospitals, while previous studies used smaller samples and were conducted only in urban centers.…”
Section: Discussioncontrasting
confidence: 58%
“…which comparatively higher than (12.3%) the finding on this study but in modern obstetrics having obstructed labor is completely obsolete [25]. In this study there were seven (8.6%) CS done without justified medical indication according the criteria based audit which is similar with report from Addis Ababa (6.9%) [16] but lower than the report from Tanzania (19.5%), global survey by WHO (14.2%) and china (69%). This might be due to clinicians/physicians' clinical decision making skills difference [5,26].…”
Section: Discussionsupporting
confidence: 81%
“…This discrepancy might be due to differences in the study area and most of the above study was conducted in specialized referral teaching hospitals [16][17][18][19][20]. Our survey finding was also far below the global figure, North America (32.3%), Oceania (31.1%), Europe (25%), Asia (19.2%) but above the African rate of CS (7.3%) [21].…”
Section: Discussionmentioning
confidence: 56%
“…The results obtained by the researcher are in line with the research conducted by Bayou, Mashaalla, & Tshweneagae, (2015) which is one of the causes of caesarean section delivery is the request of the mother or family.…”
Section: Secondary Data 2017supporting
confidence: 81%